2011
DOI: 10.1177/1077801211407289
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Comprehensive Services in Substance Abuse Treatment for Women With a History of Intimate Partner Violence

Abstract: This study examines the impact of comprehensive services on posttreatment substance use among women with a history of intimate partner violence. The sample includes 1,123 women from 50 treatment facilities derived from the National Treatment Improvement Evaluation Study (NTIES). Generalized linear mixed modeling was used to determine whether a history of intimate partner violence moderates the association between service receipt and posttreatment substance use. Significant interactions were found between histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…These findings extend those of earlier studies that documented the effects of IPV on increasing women’s drug use, and build on the few existing studies that documented the negative effect of victimization on drug intervention outcomes among women [3234] Specifically, we found that even after controlling for other factors associated with drug use abstinence, experiencing IPV or non-partner victimization was associated with a 40 % decreased likelihood of achieving abstinence. The deleterious effects of victimization on drug abstinence is also a particular concern given that continuing drug use among women participating in an HIV risk-reduction program is likely to impact negatively on HIV prevention goals.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings extend those of earlier studies that documented the effects of IPV on increasing women’s drug use, and build on the few existing studies that documented the negative effect of victimization on drug intervention outcomes among women [3234] Specifically, we found that even after controlling for other factors associated with drug use abstinence, experiencing IPV or non-partner victimization was associated with a 40 % decreased likelihood of achieving abstinence. The deleterious effects of victimization on drug abstinence is also a particular concern given that continuing drug use among women participating in an HIV risk-reduction program is likely to impact negatively on HIV prevention goals.…”
Section: Discussionsupporting
confidence: 87%
“…The few studies that have examined whether experiences of partner violence inhibit women’s ability to stop using drugs support assertions that women with histories of partner victimization have poorer treatment outcomes than women without experiences of violence [3134]. However, relatively little has been published on the effects of non-partner gender-based violence on drug use outcomes [35].…”
Section: Introductionmentioning
confidence: 99%
“…Using, procuring and sharing drugs have, in fact, been underlined as sources of dispute and aggressiveness (Gilbert, El-Bassel, Rajah, Foleno, & Frye, 2001). This kind of setting in which both partners are drug users may also have negative effects on communication skills, facilitating the intensification of violence during arguments (Andrews, Cao, Marsh, & Shin, 2011). …”
Section: Theoretical Models Of Substance Abuse and Intimate Partner Vmentioning
confidence: 99%
“…This bidirectional relation between substance use and violence shows how both factors are involved in a “cycle of spiraling losses and increasing vulnerabilities” (El-Bassel, Gilbert, Wu, Go, & Hill, 2005). In this vicious circle, re-victimization plays the significant role which links past experiences of substance-related violence with the risk of further additional abuse (Andrews et al, 2011; Rivaux et al, 2008). …”
Section: Theoretical Models Of Substance Abuse and Intimate Partner Vmentioning
confidence: 99%
See 1 more Smart Citation